"When the ground opened": Responsibility for harms and rights violations in disasters – Insights from Sierra Leone. Issue 1 (1st January 2022) - Sesay, Mohamed; Bradley, Megan
Abstract: So-called "natural" disasters are often characterized by major human rights abuses, yet responsibility and accountability for such violations have attracted relatively limited attention in research and practice. Instead, these events and survivors' suffering are often dismissed as "acts of God" or tragic misfortunes. Through analysis of an under-examined disaster—the 2017 mudslide in Freetown, Sierra Leone—this article probes survivors' perspectives on responsibility for disasters, and suffering and violations accompanying them. While survivors in this case often attribute responsibility to God or other supernatural forces, they also understand the state and other earthly actors as sharing different forms and degrees of responsibility for the disaster and its harmful consequences. Indeed, seeing the mudslide as an "act of God" does not absolve the state from its obligation to protect citizens from harms associated with disasters and subsequent response efforts. Survivors' perspectives provide significant insight into the challenge of advancing accountability in disaster contexts.